Unraveling the triglyceride-glucose index: a key predictor of liver fat content and the amplifying role of BMI: evidence from a large physical examination data - Liu, Su-Juan; Duan, Jin-Hui; Chen, Yang-Yang; Gu, Shi-Li; He, Yu-Hua; Xue, Ming-Mei; Yue, Jun-Yan (Frontiers in Endocrinology, 2025)
BackgroundThe triglyceride-glucose (TyG) index is associated with the severity of metabolic-associated fatty liver disease (MASLD), but its link to liver fat content is not fully understood. This study investigates the relationship between the TyG index and liver fat content and explores the role of body mass index (BMI) as a mediator.MethodsThis cross-sectional study analyzed data from 12,750 participants who underwent health screenings at the first affiliated hospital of Xinxiang Medical University between January 2018 and December 2023. The TyG index, derived as Ln [triglycerides (mg/dl) * fasting plasma glucose (mg/dl)/2], was the independent variable, while liver fat content, measured by quantitative computed tomography (QCT), was the dependent variable. Participants were grouped into tertiles based on their TyG index. Univariate and multivariate analyses, smooth curve fitting (generalized additive models), threshold effect analysis, and subgroup analyses were used to assess the TyG-liver fat content relationship. BMI’s mediating effect was also examined.ResultsLiver fat content increased steadily across TyG index tertiles. After adjusting for confounders, the TyG index remained independently associated with liver fat content [β = 1.42, 95% CI: 1.26-1.57]. Participants in the highest TyG tertile (T3) had a 1.58-fold higher liver fat content compared to those in the lowest tertile (T1) (95% CI: 1.37-1.80, P<0.001). A generalized additive model showed a nonlinear relationship between TyG index and liver fat content. When the TyG index ≤ 7.39, liver fat content increased gradually (β = 0.74, 95% CI: 0.50-0.99, P<0.001). Beyond this threshold, liver fat content rose sharply (β = 2.19, 95% CI: 1.92-2.46, P<0.001). Subgroup analysis indicated that the association between TyG index and liver fat content was stronger at higher BMI levels (P for interaction < 0.001). Mediation analysis revealed that BMI accounted for 26.68% of the observed effect.ConclusionThe TyG index is positively associated with liver fat content in a nonlinear manner, with BMI amplifying this effect. These results suggest that the TyG index may be a useful marker for predicting liver fat content, and managing weight could help slow the progression of MASLD.